Ultrasound evaluation of the Achilles enthesis in inflammatory and non-inflammatory processes: a systematic review and meta-analysis - Desai, Nancy; Baker, Joshua F; Bucci, Justin; Kissin, Eugene Y (Clinical and experimental rheumatology, 2023)
Ultrasound evaluation of the Achilles tendon has been utilised to assess involvement at the entheses in the setting of various inflammatory, metabolic, and mechanical processes. The purpose of this systematic review was to evaluate the differences in ultrasound findings at the Achilles enthesis between inflammatory tendinopathy (IT) versus non-inflammatory tendinopathy (NIT). A review of all studies involving ultrasound evaluation of IT or NIT (mechanical or metabolic) affecting the Achilles enthesis was performed by searching the Embase, PubMed and Medline databases from start until October 2020. We assessed study quality and extracted summary data from each individual study. We used random-effects meta-analysis to determine the average proportion of affected anatomic sites across all studies for each abnormality, weighting the analysis based on the size of each individual study. Achilles enthesis thickening was more frequent in the symptomatic IT (sIT) group (37.8%) compared to the unspecified IT (25%), NIT (11.2%) and healthy control (2.7%) groups. Increased vascularity at the enthesis was more common in the NIT (23.4%) group compared to the IT (9%), sIT (8.6%) and healthy control (0.1%) groups. Erosions were more common among the IT (17.3%) and sIT (14%) groups compared to the NIT (2.2%) and healthy controls (0.3%) groups. While Achilles enthesis thickening, Doppler signal and calcaneal erosions discriminate IT from healthy subjects, erosions are more likely to distinguish IT from NIT than thickening or Doppler signal. Additional study is needed to quantify the diagnostic performance of ultrasound at this location given the frequency of abnormalities in NIT.